Regional Integration: Do intra-African trade and migration improve income in Africa? - (:unkn) unknown (My University, 2018)
Regional integration in Africa is a subject of great interest, but its impact on income has not been studied sufficiently. Using cross-sectional and panel estimations, this paper examines the impact of African integration on real per capita income in Africa. To do this, we consider intra-African trade and migration flows as quantitative measures reflecting the intensity of regional integration. In order to address the endogeneity concerns, we use a gravity-based IV strategy. Our results show that, from a long-term perspective, African integration has not been strong enough to generate a positive, significant and robust impact on real per capita income in Africa. However it appears to be significantly income-enhancing in the short term but only through inter-country migration. These results are robust to a wide range of specifications. Further analysis shows that economic diversification, financial development and the quality of transport and telecommunication infrastructure significantly affect the impact of intra-African trade on per capita income. Their improvement would make intra-African trade income-improving. Our policy recommendations have been formulated in this direction.
Keywords: African Research